From Community to Public Familiarity: Neighborhood, Sociability, and Belonging in the Neoliberal City. Issue 4 (July 2022) - Link, Felipe; Señoret, Andrés; Valenzuela, Felipe
Current urban neoliberalism processes have shaped and changed contemporary cities, including the local scale's built environment and social relations. This article aims to study how such transformations affect local sociability by analyzing the effects of neighborhoods' morphology and socio-demographic characteristics on different forms of interactions and how they affect the sense of belonging. Taking the Metropolitan Area of Santiago, Chile, as a case study, we gathered secondary data on urban morphology and surveyed ten neighborhoods to measure sociability patterns. The results obtained from multilevel logistic regression models show that time living in the neighborhood and public pedestrian space is the most critical factor affecting neighborhood sociability. Moreover, instead of local ties, public familiarity is the form of sociability with the most substantial effects on a sense of belonging. We conclude that recent neighborhoods, formed by neoliberal urbanization, tend to discourage neighborhood sociability and a sense of belonging.